2020
DOI: 10.1159/000510501
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile of the Logopenic Variant of Primary Progressive Aphasia Using the <b><i>Dépistage Cognitif de Québec</i></b>

Abstract: <b><i>Background/Aims:</i></b> The logopenic variant of primary progressive aphasia (lvPPA) is characterized by impaired word-finding and sentence repetition with phonologic errors but spared motor speech and grammar and semantic knowledge. Although its language deficits have been well studied, the full spectrum of cognitive changes in the lvPPA remains to be defined. We aimed to explore the neurocognitive profile of the lvPPA using a newly developed cognitive screening tool for atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In all three PPA variants, studies that assessed cognition reported a decline over time. Previous studies have indeed demonstrated that even if language is primarily affected in PPA, other cognitive functions are impaired as well [5,[52][53][54]. Regardless of the variant, two studies described a faster decline in cognition for PPAs, when compared to AD [25,34].…”
Section: Similarities Between All Three Main Variants Of Ppamentioning
confidence: 95%
“…In all three PPA variants, studies that assessed cognition reported a decline over time. Previous studies have indeed demonstrated that even if language is primarily affected in PPA, other cognitive functions are impaired as well [5,[52][53][54]. Regardless of the variant, two studies described a faster decline in cognition for PPAs, when compared to AD [25,34].…”
Section: Similarities Between All Three Main Variants Of Ppamentioning
confidence: 95%